HEALTH TOURISM - EVOLUTIONS AND PERSPECTIVES - GABRIELA, SLUSARIUC (Revista de turism - studii și cercetări în turism, 2020)
This study presents the evolution of health tourism from antiquity to the present, and tries to highlight a conceptual analysis of health tourism, given its complexity of influence on the physical and mental level, from conception to the end of life, including all the aspect of life, physically and mentally